Plagiarism, Self-Efficacy, and Academic Procrastination on University Students - Baidi Bukhori; Darmu’in Darmu’in (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
The study aims to examine the effect of academic self-efficacy and academic procrastination on plagiarism behavior in students. The population of this research is the students of Walisongo State Islamic University Semarang from 2nd to 12th semester. Sampling was carried out by using the stratified sampling method, and 388 students were obtained. Data were collected using three scales: the plagiarism behavior scale, the academic self-efficacy scale, and the academic procrastination scale. Moreover, the data collected was analyzed using multiple regression analysis techniques. The result of the data analysis showed that academic self-efficacy and academic procrastination simultaneously influence the behavior of plagiarism. The higher the academic self-efficacy and the lower the academic procrastination, the lower the plagiarism behavior, conversely the lower the academic self-efficacy and the higher the academic procrastination, the higher the plagiarism behavior. The contribution of academic self-efficacy variables and academic procrastination simultaneously in explaining plagiarism variables was 13%.